Shockwaves delivery for aortic valve therapy—Realistic perspective for clinical translation? - Curini, Lavinia; Pesce, Maurizio (Frontiers in Cardiovascular Medicine, 2023)
Calcific aortic valve disease (CAVD) is the most frequent valvular heart disorder, and the one with the highest impact and burden in the elderly population. While the quality and standardization of the current aortic valve replacements has reached unprecedented levels with the commercialization of minimally-invasive implants and the design of procedures for valve repair, the need of supplementary therapies able to block or retard the course of the pathology before patients need the intervention is still awaited. In this contribution, we will discuss the emerging opportunity to set up devices to mechanically rupture the calcium deposits accumulating in the aortic valve and restore, at least in part, the pliability and the mechanical function of the calcified leaflets. Starting from the evidences gained by mechanical decalcification of coronary arteries in interventional cardiology procedures, a practice already in the clinical setting, we will discuss the advantages and the potential drawbacks of valve lithotripsy devices and their potential applicability in the clinical scenario.